Alemanha Oriental: modos de lembrar - Oliveira, Juliana Alvim de (2016)
Even after almost 27 years since the fall of the Berlin Wall, the memory of East Germany is still disputed. Its appropriation today happens mainly through ‘museumization’ and the marketing of symbols from the past, but individual memories are still sufficiently powerful to prevent forgetting through consumerism. In this dissertation, I seek to approach different ways of remembering East Germany through testimonies of people who, in very distinctive ways, lived the socialist regime that ended with the country’s unification with West Germany in 3 October 1990. I also intend to present a foreign outlook into Berlin’s complexities and its commitment to not forgetting its difficult past